PERAN BALAI KONSERVASI SUMBER DAYA ALAM DALAM PERLINDUNGAN TAMAN WISATA GUNUNG BAWAKARAENG: Perspektif Undang-Undang Nomor 5 Tahun 1990 dan Siyasah Syar’iyyah - Fajriah, Fajriah; Gassing HT, A. Qadir (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The rich biodiversity in Indonesia encourages conservative regional management through Nature Parks. The serious threat of biodiversity damage brings an important role for the Natural Resources Conservation Agency to carry out efforts to protect and control biodiversity based on Law Number 5 of 1990. Research is qualitative research. The results showed that the role of the Natural Resources Conservation Center (KSDA) in carrying out the conservation of biological natural resources and ecosystems in the natural tourism park of the Bawakaraeng Mountain Area based on Law Number 5 of 1990 has gone through the stages of protection, preservation, and utilization, and in its implementation, there are obstacles, such as human resources, facilities, and facilities, community, and culture. From the perspective of siyasah syar’iyyah, the protection of natural tourism parks cannot be separated from human treatment, so in fact humans including society and the government must provide a balance value between other creatures of Allah with the preservation actions that have been required by the Quran and hadith.